Peran Tokoh Adat dalam Keputusan Kesehatan tentang Program KB di Desa Kenyabur Baru, Kabupaten Sintang: Perspektif Strukturalisme Sosiologi - Barliy Brasila; Rizki Amartani; Yolanda Montessori; Lea Masan; Akhmad Hasan; Silvia Finida Hannisa (CV Global Research Publication, 2026)
This study aims to analyze the role of traditional leaders in health decision-making regarding the Family Planning (KB) program in Kenyabur Baru Village, Sintang Regency, through the perspective of structural functionalism. Using a qualitative method with a descriptive approach, data were collected through in-depth interviews with Dayak and Javanese traditional leaders, village government officials, health workers, and the local community. The results indicate that the success of the KB program in this region is driven by the fulfillment of four functional prerequisites in the AGIL scheme (Adaptation, Goal Attainment, Integration, and Latency). Traditional leaders play a central role in the integration function by aligning government policies with traditional values, ensuring that the KB program is accepted as part of moral responsibility and orderly living rather than structural coercion. The tripartite synergy between traditional authorities, the village government, and health workers creates an equilibrium that minimizes social resistance and strengthens cultural legitimacy toward modern healthcare service.